Effects of bovine lactoferrin on the immature porcine intestine. Issue 2 (28th January 2014) - Nguyen, Duc Ninh; Li, Yanqi; Sangild, Per T.; Bering, Stine B.; Chatterton, Dereck E. W.
<x content-type="archive" xml:space="preserve">Abstract</x> Bioactive milk proteins may be important in protecting preterm infants from developing inflammation and necrotising enterocolitis (NEC). A preterm pig model was used to investigate the protective effects of enteral bovine lactoferrin (bLF) against NEC development and inflammation. Caesarean-delivered preterm pigs were fed parenteral and minimal enteral nutrition for the first 2 d followed by 2 d of total enteral nutrition before euthanasia. Pigs were stratified into two groups and fed with either a control formula (CON, n 15) or a 10 g/l of bLF-enriched formula (LF, n 13). NEC incidence, gut functions and inflammatory cytokines were analysed. NEC incidence and nutrient absorption were similar between the two groups. In pigs that developed NEC, disease outcome was more severe in the colon accompanied by increased intestinal permeability in LF pigs. In contrary, the LF pigs had a lowered IL-1β level in the proximal small intestine. Dose-dependent effects of bLF on cell proliferation, intracellular signalling and cytokine secretion were tested in porcine intestinal epithelial cells (PsIc1) in vitro. Low doses (0·1–1 g/l) increased cell proliferation via extracellular signal-regulated kinase (ERK), limited IL-8 secretion and prevented NF-κB and hypoxia-inducible factor-1α (HIF-1α) activation, suggesting anti-inflammatory effects. In contrast, at a higher dose (10 g/l), bLF exerted adverse effects by reducing cell proliferation, stimulating IL-8 release, inhibiting ERK activation and up-regulating NF-κB and HIF-1α activation. Overall, at a dose of 10 g/l, bLF exacerbated disease severity in pigs that developed NEC, while the in vitro studies indicated the positive effects of bLF at low doses (0·1–1 g/l). Supplementation of infant formulas with bLF should therefore be optimised carefully.